ANALISIS PERMINTAAN TENAGA KERJA PADA PERUSAHAAN PERKEBUNAN SAWIT (Studi Kasus PT.SOCFINDO Perkebunan Seunagan Kabupaten Nagan Raya) - Leli Putri Ansari (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2018)
AbstractThis study aims to analyze the effect of wages and production on oil palm plantation companies, a case study of PT.Socfindo Seunagan  Nagan Raya district. This research methode uses multiple liniear regression data analysis model. This research is quantitative and time series data for the period of 2005-2016 and data in the form of secondary data obtained from PT.Socfindo Seunagan  Nagan Raya district and Central Bureau of statistics (BPS) Nagan Raya district.Based on the results of research partial testing that wages have a significant influence on labor for demand. Where as production has no significant effect on the demand  for labor. Simultaneous testing that wages and production effect labor for demand Keyword: Wage, production, and labor for demand